2015
DOI: 10.1016/j.drugalcdep.2015.02.032
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of methamphetamine self-administration in male and female rats

Abstract: Background Because methamphetamine (METH) pharmacokinetics after single iv doses show significant differences between male and female rats, we hypothesized that pharmacokinetic differences in METH disposition could be a contributing factor to the patterns of METH self-administration behaviors in rats. Methods For the studies, we used a passive (non-contingent) METH dosing schedule consisting of 27 METH iv bolus injections (0.048 mg/kg) over 2 hrs derived from a previous active (contingent) METH self-administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
1
13
1
Order By: Relevance
“…Females pressed the METH-associated active lever less and received fewer METH infusions during self-administration training, when compared to our previous experiments with males. While we have not made direct, statistical comparisons because the experiments were not performed side-by-side, this is consistent with previously published studies demonstrating a greater sensitivity to psychostimulants in females, likely due to greater bioavailability [24]. Another sex difference noted when comparing the current data in females to our prior data in males is related to BLC spine density.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Females pressed the METH-associated active lever less and received fewer METH infusions during self-administration training, when compared to our previous experiments with males. While we have not made direct, statistical comparisons because the experiments were not performed side-by-side, this is consistent with previously published studies demonstrating a greater sensitivity to psychostimulants in females, likely due to greater bioavailability [24]. Another sex difference noted when comparing the current data in females to our prior data in males is related to BLC spine density.…”
Section: Discussionsupporting
confidence: 89%
“…For instance, women tend escalate to addiction faster, and be more susceptible to feelings of craving and relapse, relative to men [1823]. Moreover, greater bioavailability of psychostimulants has been shown in female animals, as compared to males, and consistent with this, females tend to self-administer lower drug doses [24]. Adolescents are another population that is under-studied and at significant risk for SUD.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a recent study found that female rats achieved a higher peak concentration of methamphetamine, and they demonstrated a lower clearance rate than male rats. 33 In the female group, there was also a significantly greater suppression of appetite and cravings, and a diminution in food consumption, during the snack-food challenge that followed administration of MP, relative to that in the placebo condition. These results are in accord with previous evidence that obese men, compared to those of normal weight and compared to both female weight groups, were relatively inured to the appetite suppression normally seen in response to psychomotor stimulant drugs.…”
Section: Sex Differencesmentioning
confidence: 92%
“…Future studies would need to modify the BDLsurgical technique to produce a range of hepatic dysfunction and study additional hepatotoxicity biomarkers to determine and characterize potential liver damage due to METH exposure. Additionally, this study was only performed in male rats, but there are known sex differences in METH-induced rat behavior and METH PK (32,(41)(42)(43) and in effects on human behavior and brain function (44).…”
Section: Discussionmentioning
confidence: 99%